Investigation of Site Dependent Donor-Acceptor (Al-N) Doping Effect into ZnO for Optoelectronic Applications - Sayed, M. A.; Kamruzzaman, M.; Liton, M. N. H.; Helal, M. A.; Rahman, M. (Journal of Scientific Research, 2024)
In this study, the density functional theory (DFT) is used to investigate the effect of the incorporation of Al (donor) in the Zn-site and N (acceptor) in the O-site of ZnO. The detailed theoretical study highlights the confirmation of p-type conductivity and bandgap (0.58 and 0.21 eV) narrowing exhibits in N- and (Al-N)-doped ZnO systems. p-type nature is explicitly observed by introducing acceptor bands at the top of the valance band (VB). Whereas, degenerate n-type conductivity is seen in Al-doped ZnO and a widened bandgap of 2.70 eV is attributed to Burstein-Moss (BM) effect. The calculated value of the effective mass of the (Al-N)-doped ZnO system is lower than that of the un-doped ZnO. Enhancement of the absorption and photoconductivity in the visible region for N- and (Al-N)-doped ZnO could be due to the availability of more density of states. Importantly, reflectivity, refractive index, transmittance, dielectric constants, and optical band gap have also been calculated. Higher transmittance of the samples suggested that these could be suitable for the window material of solar cells. The optical bandgap value supports the electronic bandgap value. Therefore, our finding would be helpful to design high-performance homo-junction based electronic and optoelectronic devices.